ANALISIS OF OUTPATIENT SATISFASION ON QUALITY OF PHARMACY SERVICE IN PHARMACY X (STUDY ON NOVEMBER 2011) - Enggar Anitawati; Achmad Fudholi; Sumarni Sumarni (Faculty of Pharmacy, Universitas Gadjah Mada)
One indicator of the success of individual health care is patient satisfaction. Customer satisfaction was defined as a response to evaluate the expectations of service prior to the actual performance perceived. The aimed of this study were to know the quality of outpatient satisfaction and to know the gap on outpatient satisfaction to the quality of based on servqual dimensions, that is tangible, empathy, assurance, responsiveness andreliability in study. The method of this study was a non experimental descriptive through observation of patient satisfaction. Data were collected with concurrent in sampling technique respondens. Data were collected with a questionnaire in November 2011. Data were analized with instrument using Product Moment Persons corelation, continued with calculation of servqual score gap betwen performance and expectation. The results showed that the perceived service was not achieve the desired expectations of patients. Largest gap value is showed on the dimension of empathy with a value of -0.27. Meanwhile, the gap value on tangible, assurance, reliability, and responsiveness dimension were -0.25, -0.17, -0.16, -0.15 respectively.Keywords: Service quality, satisfaction, gap, on an out patient basis have not beenable to satisfy